FEATURES OF WORD FORMATION. (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
The main purpose of writing this article is word formation and its thinking about types, methods of making. Today's word formation structure assess its completeness. Types and methods of word formation for students delivery, formation, growth, based on the required level of literacy ensure proper and reasonable use of Uzbek language opportunities issues are covered in this article.